Association of dietary patterns and sarcopenia in the elderly population: a cross-sectional study - Wang, Boshi; Wei, Yanan; Shao, Lin; Li, Menghan; Zhang, Xue; Li, Wei; Zhao, Shilong; Xia, Xin; Liu, Peng (Frontiers in Aging, 2023)
Background: Sarcopenia, defined as the loss of muscle mass and strength, has been associated with increased hospitalization and mortality. Dietary pattern analysis is a whole diet approach which in this study was used to investigate the relationship between diet and sarcopenia. This study aims to estimate the prevalence of sarcopenia and explore possible factors associated with it among a large population in Beijing, China. Methods: A cross-sectional study with 1,059 participants aged more than 50 years was performed. Sarcopenia was defined based on the guidelines of the Asian Working Group for Sarcopenia. The total score of the MNA-SF questionnaire was used to analyse nutrition status. The baseline demographic information, diet structure and eating habits were collected by clinicians trained in questionnaire data collection and anthropometric and bioimpedance measurements. Results: The overall prevalence of sarcopenia was 8.8% and increased with age: 5%, 5.8%, 10.3% and 26.2% in the 50–59, 60–69, 70–79, and ≥80 years groups, respectively. Marital status (with or without a spouse) was not an independent factor associated with sarcopenia adjusted by age and sex. However, nutritional risk or malnutrition, vegetable diet, advanced age and spicy eating habits were risk factors for sarcopenia. Meanwhile, daily fruit, dairy and nut consumption were protective factors against sarcopenia adjusted by age, sex, income status and spouse status. Conclusion: Although further studies are required to explore the association between healthy dietary patterns and the risk of sarcopenia, the present study provides basic data for identifying correlates of sarcopenia in elderly Chinese individual.